Evaluation of mucosal adjuvants to chitosan-nanoparticle-based oral subunit vaccine for controlling salmonellosis in broilers - Suresh, Raksha; Olaitan Comfort, Shekoni; Dolatyabi, Sara; Schrock, Jennifer; Singh, Mithilesh; Renukaradhya, Gourapura J. (Frontiers in Immunology, 2025)
Salmonellosis, a gastrointestinal disease, continues to be one of the major public health concerns worldwide. Poultry meat and eggs are recognized as the major source of Salmonella food poisoning in humans. Our study evaluated the protective efficacy of mannose-conjugated chitosan-nanoparticle (mChitosan-NP)-based subunit vaccine, consisting of immunogenic outer membrane proteins and flagella of Salmonella Enteritidis [mChitosan (OMP+FLA)/FLA-NP], coadministered orally with potent mucosal adjuvants to reduce the colonization of S. Enteritidis in the intestines of broiler chickens. We evaluated the adjuvant effects of three different doses of two well-known mucosal adjuvants, c-di-GMP (stimulator of interferon gene agonist) and whole cell lysate (WCL) of Mycobacterium smegmatis, to improve the efficacy of mChitosan (OMP+FLA)/FLA-NP vaccine. Our data reaffirmed the potent adjuvanticity of both of these adjuvants and identified their optimal dose when entrapped in mChitosan-NP to potentiate the immunogenicity and efficacy of orally delivered mChitosan (OMP+FLA)/FLA-NP vaccine. The physical characteristics of mChitosan (OMP+FLA)/FLA-NP, mChitosan-GMP/FLA-NP, and mChitosan-WCL/FLA-NP formulations revealed a high positive charge (Zeta potential +20–25 mV), size 235–260 nm, and polydispersity index 0.35–0.52, which are conducive for oral delivery. The efficacy in chickens that received oral administration with a combination of the vaccine-adjuvant formulations was evaluated by challenging with Salmonella Enteritidis. Our data showed that mChitosan (OMP+FLA)/FLA-NP WCL at 10 µg/dose formulation consistently reduced the S. Enteritidis load by over 0.5 log10 comparable to a commercial live vaccine at post-challenge days 4 and 10. Immunologically, we observed enhanced systemic and mucosal antibody and cellular (B cells and T-helper cells) immune responses as well as upregulation of expression of immune cytokine genes IFN-γ, TGF-β, and IL-17 in the cecal tonsils of adjuvanted mChitosan-NP Salmonella-subunit-vaccinated birds. Overall, particularly the mucosal adjuvant WCL consistently enhanced the efficacy of mChitosan (OMP+FLA)/FLA-NP vaccine by inducing effective immune responses.